2017
DOI: 10.1080/0284186x.2017.1309063
|View full text |Cite
|
Sign up to set email alerts
|

Adverse events in hospitalised cancer patients: a comparison to a general hospital population

Abstract: Background: Patients with cancer are often treated by many healthcare providers, receive complex and potentially toxic treatments that can increase the risk for iatrogenic harm. The aim of this study is to investigate whether hospitalised cancer patients are at higher risk of adverse events (AEs) compared to a general hospital population. Material and methods: A total of 6720 patient records were retrospectively reviewed comparing AEs in hospitalised cancer patients to a general hospital population in Norway, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 18 publications
1
21
0
Order By: Relevance
“…Similar to other studies we find that medication harms and healthcare acquired infections were the most common adverse events [22,33], but their occurrences differed between the groups. While healthcare acquired infections contributed to death of cancer patients in both groups, anticancer treatment related adverse events, contributing to death only occurred in patients who received such treatment during the last 30 days of life.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar to other studies we find that medication harms and healthcare acquired infections were the most common adverse events [22,33], but their occurrences differed between the groups. While healthcare acquired infections contributed to death of cancer patients in both groups, anticancer treatment related adverse events, contributing to death only occurred in patients who received such treatment during the last 30 days of life.…”
Section: Discussionsupporting
confidence: 90%
“…This included all types of adverse events whether caused by systemic anticancer treatment, other medications or healthcare acquired infections. In a previous study we found that hospitalised cancer patients had an increased risk of adverse events in general compared to other hospitalised patients, and that they more often experienced adverse events related to medications [22].…”
Section: Discussionmentioning
confidence: 84%
“…Patients with cancer experience adverse events more frequently than other hospital patients. 1 Safety in healthcare is often described as a moving target and that numerous stakeholders are involved in keeping patients safe. 2 Families and next of kin are described as important safety experts but are rarely included in the patient's medical team.…”
mentioning
confidence: 99%
“…Patients dying in the hospital are a highly selected group of patients who are older, stay longer, are mainly emergency admissions and have a smaller range of primary diagnoses. From a previous study, we know that the risk of adverse events increases by 1.3% for every year increase in age and 5.1% for each day spent in the hospital 21. To have a representative population, we argue that measuring adverse events contributing to death should be based on inpatient deaths rather than generalisation of reviews of general hospitalised patients.…”
Section: Discussionmentioning
confidence: 99%